Effect of supplementation of Calsporin (Bacillus subtilis C-3102) during gestation and lactation on sow and piglet performance until weaning - Braun, Michaela B.; Menegat, Mariana Boscato; Lerner, Anne B.; DeRouchey, Joel M.; Dritz, Steven S.; Woodworth, Jason C.; Tokach, Michael D.; Goodband, Robert D. (My University, 2018)
A total of 29 multiparous sows (Line 241; DNA, Columbus, NE) were used in a 106-d study to determine the effect of Calsporin (Quality Technology International, Inc., Elgin, IL) on sow and litter performance. Calsporin is a direct-fed microbial product based on viable spores of Bacillus subtilis C-3102. At d 30 of gestation, sows were assigned to treatments according to body weight (BW) and parity. Treatments consisted of a control diet or a diet supplemented with Calsporin at 500,000 CFU/g of complete feed in gestation and 1,000,000 CFU/g in lactation. Sow BW was collected on d 112 of gestation, farrowing, and weaning on d 19 of lactation. Piglet BW was collected at birth, on d 2 and 12 of lactation, and at weaning. Fecal scoring was conducted on d 2 and at weaning to categorize the fecal consistency using a scale from 1 to 5 with 1 indicating hard formed feces and 5 watery feces. Data were analyzed using a linear mixed model (PROC GLIMMIX, SAS®) where treatment served as fixed effect and block as random effect. There was no evidence for differences (P>0.05) on sow BW during gestation and lactation or BW loss in lactation. There was a marginal response (P<0.056) in sow ADFI during lactation of sows fed Calsporin over the control (13.7 vs. 13.1 lb/d). There was no evidence for differences (P>0.05) on piglet BW, weight gain, or percent weaned. A reduction in fecal firmness indicated by a marginal increase (P<0.081) in fecal scores on d 2 of piglets from sows fed Calsporin over those fed a control lactation diet. This study suggests that inclusion of Calsporin does not impact sow or piglet performance until weaning but there are marginal effects on sow ADFI during lactation and fecal consistency of piglets on 2 after birth.
Keywords: Spring 2018